Analisis Pengaruh Infrastruktur Logistik, Biaya Transaksi, serta Kinerja Ekspor terhadap Efisiensi Ekspor Cengkeh Indonesia - Dika Ibnu Pratama; Denny. Saputera (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
“This study aims to analyze the effects of logistics infrastructure, transaction costs, and export performance on the efficiency and productivity of Indonesian clove exports. A quantitative approach was employed using time series data consisting of 17 observations, analyzed through multiple linear regression. The results indicate that logistics infrastructure does not have a significant effect on either export efficiency or export productivity. In contrast, transaction costs have a negative and significant effect on both efficiency and productivity, indicating that high administrative, customs, and logistics costs reduce the performance of clove exports. Export performance has a positive and significant effect on export efficiency and productivity, while export efficiency also positively influences export productivity. Simultaneously, logistics infrastructure, transaction costs, and export performance significantly affect the efficiency and productivity of Indonesian clove exports. These findings highlight the importance of reducing transaction costs and improving export performance to enhance the competitiveness of Indonesian clove exports in the global market.”